Destruction of cultural heritage and armed conflicts. Focus on Africa - HERȚA, Laura-Maria (Presa Universitară Clujeană, 2025)
A great deal of literature focused on the transformation of warfare, the changing nature of belligerence, as spurred by globalization and by the ending of the Cold War bipolar order. Scholars1 theorized and analysed the so-called “new wars” and concentrated on the characteristics of intra-state armed violence occurring at the beginning of the post-Cold War era. Others emphasized the prevalence of civil wars.2 Many such approaches identified a changing strategy in internal armed conflicts, by focusing on ethnic cleansing, on systematic attacks carried out against unarmed civilians, on forced recruitment of children, on sexual violence carried out against women, on forced displacement of populations, on deliberate attacks on cemeteries, cultural heritage, historic buildings, archives, places of worship, and on historical sites, in general. Therefore, the main arguments presented in this book revolve around a changing dynamic and strategy in recent and contemporary armed conflicts, which are internal (not international) and which feature attacks on civilians, on communities, on the links of ethnic, religious, identity groups (in general) to certain geographic areas or the social and historical developments in some territories.